Penggunaan Wordpress Sebagai Alat Bantu Online Shop - Isma Ahmad Yulizar (Jurnal Gemilang Informatika (GIT), 2024)
In the current era of information technology, information absorption behavior is starting to shift from paper information to information technology. Many searches for information come from cyberspace/web. The use of web technology is not only used by business people or offices but is also used by educational circles. Blog owners compete with each other to increase their popularity in cyberspace. Several methods and methods are carried out. One way is to try to place it in the first position when searched on a search engine (Google). With certain keywords, how can the school website occupy the first position, at least on the first page. The more keywords that can be indexed by search engines, the more information conveyed will be visited and the more popular the website will be. The method used in SEO (search engine optimization) / Search Engine Optimization is the technique for attracting visitors to visit the site through searches in search engines. Google is one of the most widely used search engines today, so the SEO method that will be discussed here is optimization for Google on WordPress blogs. By implementing SEO on a website or blog, it is hoped that the campus website or blog will be on the front page of Google and visitors to the website or blog will increase so that the popularity of the school/campus will increase